2011
DOI: 10.37236/682
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Brooks' Theorem for Digraphs of Girth at least Three

Abstract: Brooks' Theorem states that a connected graph G of maximum degree ∆ has chromatic number at most ∆, unless G is an odd cycle or a complete graph. A result of Johansson [6] shows that if G is triangle-free, then the chromatic number drops to O(∆/ log ∆). In this paper, we derive a weak analog for the chromatic number of digraphs. We show that every (loopless) digraph D without directed cycles of length two has chromatic number χ(D) ≤ (1 − e −13 )∆, where∆ is the maximum geometric mean of the out-degree and in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…This notion of colorings of digraphs turns out to be the natural way of extending the theory of undirected graph colorings since it provides extensions of most of the basic results from graph coloring theory [3,7,8,14,15].…”
mentioning
confidence: 99%
“…This notion of colorings of digraphs turns out to be the natural way of extending the theory of undirected graph colorings since it provides extensions of most of the basic results from graph coloring theory [3,7,8,14,15].…”
mentioning
confidence: 99%
“…Regarding digraphs, Erdős [7] conjectured that χ(D) = O( ∆(D) log 2 ∆(D) ) for digon-free digraphs, whereas ∆(D) denotes the maximum total degree of D. To the knowledge of the authors, this conjecture is still open. Related to this question, Harutyunyan and Mohar [9] proved the following. Given a digraph D, let∆(D)…”
Section: Discussionmentioning
confidence: 95%
“…By taking m = 1 in Theorem 2.10, we obtain Corollary 1.5. Harutyunyan and Mohar [10] posed the question of determining the smallest integer ∆ 0 such that every oriented graph D with ∆ (D) = ∆ 0 satisfies χ A (D) ≤ ∆ 0 − 1. They showed that ∆ 0 exists and is at most some integer which is approximately equal to 10 10 , and they also proved that ∆ 0 ≥ 4.…”
Section: Let D Be the Subgraph Induced By The Set Of Allmentioning
confidence: 99%
“…Harutyunyan and Mohar [10] applied the probabilistic method to digraphs to show that χ A (D) ≤ (1−e −13 )∆(D) for∆(D) large enough, which only slightly improves upon the trivial bound of χ A (D) ≤ ∆ (D) + 1 and is far from the bound given in Conjecture 1.1. They also posed the following related conjecture, which, although much weaker than Conjecture 1.1 for∆(D) large, gives a precise bound for all∆(D), unlike Conjecture 1.1.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation